2016
DOI: 10.3329/bjmm.v1i2.21511
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Contraceptives on Prevalence of Candida Species on Vaginal Candidiasis in Dhaka, Bangladesh

Abstract: This study was designed to find out the relationship between uses of different contraceptives and the prevalence of vaginal candidiasis. High vaginal swabs were obtained from 350 women in the age group of 15-45 years with vaginal discharge attending at Sir Salimullah Medical College Hospital, Dhaka, which comprised of 247 contraceptive users & 103 non-contraceptive users. A detailed clinical history and a thorough examination of all the cases were done. After making the clinical diagnosis, appropriate test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
1
6
0
5
Order By: Relevance
“…Vaginal candidiasis is a common vaginal infection attributed to different species of Candida of 88 symptomatic women, 50 (56.8%) were diagnosed as vaginal candidiasis infection with a higher prevalence rate than that reported by several researchers (Paulitsch et al, 2006;Yusuf et al, 2007 andOgouyèmi-Hounto et al, 2014). In this work, C. albicans was the predominant cause of vaginal candidiasis, followed by C. tropicalis, C. glabrata and C. krusei.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Vaginal candidiasis is a common vaginal infection attributed to different species of Candida of 88 symptomatic women, 50 (56.8%) were diagnosed as vaginal candidiasis infection with a higher prevalence rate than that reported by several researchers (Paulitsch et al, 2006;Yusuf et al, 2007 andOgouyèmi-Hounto et al, 2014). In this work, C. albicans was the predominant cause of vaginal candidiasis, followed by C. tropicalis, C. glabrata and C. krusei.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, several researches were done to clarify the prevalence of different vulvovaginal Candida to age, educational level, work, personal hygiene and contraceptive method of the women (Yusuf et al, 2007;Rezaei-Matehkolaei et al, 2016 andSwaminathan et al 2017). The current study showed that the maximum incidence of vaginal candidiasis was found between youths (20-34 age), the rate of vaginitis was decreased by increasing educational level and the douching using women were more susceptible to the risk of infection with vaginitis Candida.…”
Section: Discussionmentioning
confidence: 99%
“…Diperkirakan sekitar 20% populasi wanita di dunia tiap tahunnya mengalami kandidiasis serviks (19) . Angka prevalensi kandidiasis pada kelompok perempuan perilaku risiko tinggi adalah 11,2-28,9%, angka tersebut justru lebih rendah dari kelompok perempuan perilaku risiko rendah (23) .…”
Section: Pendahuluanunclassified
“…Hasil analisis tersebut menunjukkan perbedaaan yang bermakna terjadinya kandidiasis serviks antara akseptor kontrasepsi hormonal dengan non hormonal, dengan nilai p= 0,000 (p<0.001), CI= 95% dan OR= 6,435. Penelitian ini sesuai juga dengan beberapa penelitian sebelumnya yang menunjukkan hasil serupa (4,6,13,19) . Pada beberapa penelitian tersebut didapatkan bahwa kandungan estrogen maupun progesteron yang terdapat pada kontrasepsi hormonal dapat meningkatkan glikogen pada serviks dan vagina yang selanjutnya diubah menjadi asam laktat oleh laktobasilus.…”
Section: Ucapan Terima Kasihunclassified
See 1 more Smart Citation